Sosialisasi Bullying (Perundungan) Sebagai Upaya Pencegahan Terjadinya Kekerasan di SD Negeri 1 Argosuko - Azmi, Muhammad Yusrin Naufal (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to determine the impact of bullying, the factors that cause bullying, and the efforts of KKM 131 UIN Maulana Malik Ibrahim Malang in tackling bullying among students. The method used is qualitative, namely observation and lecture methods. The results showed that the form of bullying that occurred was physical bullying in the form of hitting, mocking between friends, in addition to verbal bullying in the form of cheering and calling special names to other students. The causative factors are family factors, peers and social environment. And the efforts of KKM UIN Malang and SDN 1 Argosuko in tackling bullying among students are implementing social control in the form of prevention, by holding student self-development activities, socializing bullying and discipline.